Urban vascular flora and ecological characteristics of Kadıköy district, Istanbul, Turkey - (:unkn) unknown (Maejo University, 2010)
Cities are usually considered unnatural places lacking ecological benefits. Many ecological studies have been done in suburban or rural areas and have excluded the city. However, urban ecology has become increasingly important. Today, it is well known that rapid and uncontrolled urbanisation accompanied by insufficient infrastructure has resulted in the degradation of many forests and grasslands in metropolitan areas. Land use changes due to urbanisation during the second half of the 20th century have caused widespread decline of biodiversity of many animal and plant taxa, especially in densely populated regions such as Kadi{dotless}köy district, Istanbul, Turkey. In this study, different kinds of urban habitats within the boundaries of Kadi{dotless}köy are described. Plant samples were collected, dried, labelled and identified according to standard herbarium procedures and all the greenery in the district was explored during vegetation seasons. A total of 561 vascular plant taxa were determined, wherein 412 (337 species, 44 subspecies and 31 varieties) were native and 149 (143 species and 6 varieties) were exotic and cultivated. The major native taxa were Asteraceae (46 species) while Rosaceae had the most exotics (22 species). Archaeophytes and neophytes, endemics, rare, endangered, medicinal, and poisonous species are also reported. In addition, the requirements of making ecological studies in other urban areas are mentioned. © 2010 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.
Keywords: Istanbul; Kadi{dotless}köy; Urban ecology; Urban flora; Urban habitats